Depression Levels in Yoga Practice: A Comparative Study of two Experiencing Practicing Yoga Groups During the Covid-19 Pandemic in Bali - Kumaratungga, I Wayan Mahaksa; Suparna, Ketut; Giri, Made Kurnia Widiastuti (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: Depression is a serious problem that emerged during the Covid-19 pandemic. Many people experience depression, especially those who test positive for Covid-19. The purpose of this study was to determine the difference in the level of depression in yoga practitioners with experience different durations of practicing yoga in SegerOger yoga practitioners during the Covid-19 outbreak. Methods: This research is an observational study with a cross-sectional study design. Seventy-eight respondents aged between 30 and 72 years were divided into two, namely yoga practice experience of fewer than two years and more than 2 years. Depression scores were assessed using the DASS 21. Data were analyzed using the Mann-Whitney test. Result: The results of the research on the influence of the duration of yoga practice on depression showed that the average ranking data for the group of practitioners less than 2 years was 42.32 and for the group of practitioners more than 2 years, namely 36.95. Based on the results of the statistical test, it was found that the Asymp. The Sig. (2-tailed) value of 0.164 was greater than the probability value of 0.05. Therefore, according to the decision-making basis for the Mann-Whitney U test, it can be concluded that there is no significant difference in the level of depression in yoga practitioners less than 2 years compared to more than 2 years. Conclusion: Based on the results of the study it was concluded that the duration of yoga experience does not affect the level of depression in Seger Oger Yoga practitioners.